Damage-free finishing of Lu2O3 by combining plasma-assisted etching and low-pressure polishing. Issue 1 (2022) - Lyu, Peng; Lai, Min; Liu, Ze; Fang, Fengzhou
Abstract: Lutetium oxide (Lu2 O3 ) is suitable for high-power laser matrices because of its excellent properties. However, the poor machinability greatly limits its practical applications. This work focuses on highly efficient and subsurface damage (SSD)-free machining of Lu2 O3 using a new method, namely, plasma-assisted etching, followed by low-pressure polishing. An atomically smooth and SSD-free Lu2 O3 surface is achieved with a surface roughness of 0.47 nm in Sa in 45 min. Experimental results show the laser fluence is significantly increased from 8.36 mJ/mm 2 by 80 min of conventional polishing to 17.84 mJ/mm 2 by the proposed approach, benefiting various applications in laser systems.